Consumer Spending Patterns during Economic Turbulence: A Qualitative Analysis - Shrivastava, Kamalesh Kishore (Integrated Journal for Research in Arts and Humanities, 2023)
Economic turbulence significantly affects consumer spending behavior, reshaping priorities and altering purchasing decisions. This study explores consumer spending patterns during periods of economic instability, focusing primarily on the Indian context. By employing a qualitative research methodology, the paper delves into how consumers adapt their consumption habits, prioritize essential goods over luxury items, and leverage digital platforms to navigate challenges. The analysis is complemented by real case studies and comprehensive interviews with Indian households, shedding light on the socio-economic factors driving these shifts. Recommendations aim to guide businesses and policymakers in addressing consumer needs during such periods.